Socio-demographic, behavioural and clinical factors influencing control of diabetes and hypertension in urban Mysore, South India: a mixed-method study conducted in 2018 - Sudeshna Dey; Aparna Mukherjee; Manoj Kumar Pati; Arin Kar; Satyanarayana Ramanaik; Ashwini Pujar; Vidyacharan Malve; H. L. Mohan; Krishnamurthy Jayanna; Swaroop N (BMC, 2022)
Abstract Background Inadequate control of diabetes and hypertension is a major concern in India because of rising mortality and morbidity. Few studies in India have explored factors that influence control of diabetes and hypertension. The current study aimed to improve the understanding of multifactorial influence on the control of diabetes and hypertension among patients in Primary Health Care Settings(PHC) of urban Karnataka. Methods We used a mixed-method study design, within a project aiming to improve non-communicable disease (NCD) continuum of care across PHC in Mysore city, India, conducted in 2018. The quantitative study was conducted among 399 patients with diabetes and/or hypertension and a logistic regression model was used to assess the factors responsible for biological control levels of diabetes and hypertension measured through Glycated Haemoglobin(HbA1c) and blood pressure. Further, in-depth interviews(IDI) were conducted among these patients and the counsellors at PHCs to understand the barriers and enablers for better control. Result The quantitative assessment found odds of poor control amongst diabetics' increased with older age, longer duration of disease, additional chronic conditions, and tobacco consumption. For hypertensives, odds of poor control increased with higher body mass index(BMI), alcohol consumption, and belongingness to lower social groups. These findings were elaborated through qualitative assessment which found that the control status was affected by stress as a result of family or financial worries. Stress, poor lifestyle, and poor health-seeking behaviour interplay with other factors like diet and exercise leading to poor control of diabetes and hypertension. Conclusion A better understanding of determinants associated with disease control can assist in designing focused patient outreach plans, customized communication strategies, need-based care delivery plans, and specific competency-based capacity-building models for health care workers. Patient-centric care focusing on biological, social and behavioural determinants is pivotal for appropriate management of NCDs at community level in low-middle income countries.